Genetic and epigenetic characterization of sarcoma stem cells across subtypes identifies EZH2 as a therapeutic target - Edmond O’Donnell; Maria Muñoz; Ryan Davis; Jessica Bergonio; R. Lor Randall; Clifford Tepper; Janai Carr-Ascher (npj Precision Oncology)
Abstract High-grade soft tissue sarcomas (STS) are a heterogeneous and aggressive set of cancers. Failure to respond anthracycline chemotherapy, standard first-line treatment, is associated with poor outcomes. We investigated the contribution of STS cancer stem cells (STS-CSCs) to doxorubicin resistance. We identified a positive correlation between CSC abundance and doxorubicin IC50. Utilizing patient-derived samples from five sarcoma subtypes we investigated if a common genetic signature across STS-CSCs could be targeted. We identified Enhancer of Zeste homolog 2 (EZH2), a member of the polycomb repressive complex 2 (PRC2) responsible for H3K27 methylation as being enriched in CSCs. EZH2 activity and a shared epigenetic profile was observed across subtypes and targeting of EZH2 ablated the STS-CSC population. Treatment of doxorubicin-resistant cell lines with tazemetostat resulted in a decrease in the STS-CSC population. These data confirm the presence of shared genetic programs across distinct subtypes of CSC-STS that can be therapeutically targeted.